FOREST AND LIVELIHOOD: THE NAGA TRADITIONAL PRACTICE OF PRUDENT USE OF FOREST RESOURCES FOR A SUSTAINABLE LIVELIHOOD - Zingkhai, Hormila. G. (PEOPLE: International Journal of Social Sciences, 2015)
The Nagas are one of the tribal communities from North-Eastern part of India. For the Nagas, forest is one of the most important resource systems which have nutritional, economic as well as social and cultural value in their everyday lives. As such, they are largely dependent on the forest and rely on the forest and its resources for their subsistence and livelihood. This has given rise to a well structured practice of using the forest resources efficiently and ecological knowledge that is very much linked to an engaging day- to-day experience and survival needs. However, with the high demand for timber and Non-Timber Forest Products in the global market, what remains uncertain is how long can the Nagas resist the influence of commercialisation of forest resources? In this context, the present paper focuses on the prudent use of the forest resources by the Nagas, which have helped them in conserving their forest as well as helped them in managing a sustainable livelihood. At the same time, it attempts to look into the challenges and obstacles faced by the Nagas in terms of utilizing the forest resource for their subsistence and in their effort to secure a sustainable livelihood.